DETERMINATION OF GO-FOOD WORKERS 'WAGES IN THE VEW OF YUSUF QARDHAWI: CASE STUDY OF PT. GOJEK MEDAN - Arifuddin Muda Harahap (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
This paper aims to explore the legal aspects of setting Go-Food workers' wages in the view of Yusuf Qardhawi. The place of research in this paper is in Medan, North Sumatra. This type of research is a qualitative case study method of gojek workers with the design of the legal sociology approach. The instruments used in research are observation, interviews, documentation studies and literature studies. Analysis of the data used involves three steps: data reduction, data presentation and conclusion drawing. The results of this study indicate that (1) PT.Gojek Indonesia's remuneration system is by dividing profits using 80% -20% percent. Which is the taking of wages or benefits that will be obtained by the drivers or partners when consumers pay the fees or tariffs listed on the consumer and driver's cellphone screens, (2) Go-food workers' wages are considered not in accordance with Law No.13 of 2003 Concerning Employment explains that wages given to workers must meet a decent living for workers. Wages given by PT. Gojek is not feasible and does not match what is said according to Yusuf Qardhawi and the Law, it can be concluded that the behavior of PT. Gojek is considered unfair. Keywords: Determination of Go-Food Workers’ wages, Yusuf Qardhawi View, PT                   Gojek Medan